PENERAPAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN MENULIS TEKS ANEKDOT PADA SISWA KELAS X SMA NU KAPLONGAN TAHUN PELAJARAN 2019/2020 - Rina Raudlotul Jannah; Muhammad Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to: 1) determine the effectiveness of the application of the Problem Based Learning model in learning to write anecdotal texts in grade X students of SMA NU Kaplongan Academic Year 2019/2020 and 2) How are learning activities to write anecdotal texts by applying the Problem Based Learning model to students of grade X of SMA NU Kaplongan Academic Year 2019/2020. This study uses an experimental method with a nonequivalent control group design. The population of this researcher is all students of class X of SMA NU Kaplongan for the 2019/2020 Academic Year. Using the purposive sampling technique, class X Science 2 was determined as an experimental class with a total of 22 students and class X IPS 2 as a control class with a total of 22 students. The research data was collected through written tests and observation sheets. Based on the results of statistical calculations using the Test of Normality and the difference test using the Wilcoxon test, the results of the pretest sig were 0.002 and the posttest sig was 0.004. The sig value of both is not eligible, which is ≥ 0.05. The Wilcoxon test obtained a result of 0.068 where this value ≥ 0.05. This shows that H1 is accepted and H0 is rejected, so it can be stated that the Problem Based Learning model is effectively applied in learning to write anecdotal texts in grade X students of SMA NU Kaplongan for the 2019/2020 Academic Year. Based on the analysis of observation data, it is proven that the application of the Problem Based Learning model can increase students' activity in the learning process of writing anecdotal texts in grade X students of SMA NU Kaplongan for the 2019/2020 Academic Year.